Teaching NeuroImage: Selectively Bright Inferior Cerebellum in Christianson Syndrome. (1st November 2022) - Alves, Cesar Augusto P.F.; Clifford, Simon M.; McKeown Ruggiero, Sarah; Helbig, Ingo; Chadehumbe, Madeline; Shekdar, Karuna
Abstract : A 4-year-old boy presented with developmental delay (nonverbal and unable to walk or sit independently) and recurrent tonic-clonic seizures beginning at 1 month of age. EEG demonstrated underdeveloped background organization and intermittent focal right occipital slowing. Brain MRI revealed inferior cerebellar atrophy with T2-WI and FLAIR cortical hyperintensity (Figure). A SLC9A6 c.803+3_803+6del (intronic) pathogenic variant was detected, confirming a diagnosis of Christianson syndrome (CS). CS is characterized by severe cognitive dysfunction, behavioral disorder, seizures, ataxia, and microcephaly. The condition results from loss-of-function alterations affecting sodium Na+/H+ exchange enzymes. While some clinical features may overlap with Angelman syndrome (AS), inferior cerebellar atrophy is characteristic of CS. It is important to distinguish between the 2 diagnoses because the prognosis in CS is worse than that in AS.